Optimization of Jet Impingement Erosion Process of Alumina-Titania coated stainless steels. (2022) - Kanimozhiraman,; Kennedy, Edward
Abstract: The mineral processing industries depend on conveying feed stocks in slurry form. Slurries erode the carriers as well as the pumps which are used in the process. Material loss due to erosion is a serious problem in transporting solid liquid mixture. The pump impellers are generally made of stainless steel. The efficiency of the stainless steel impellers decreases due to erosion even though the pump continues to work. These impellers are damaged or lose its efficiency roughly during 250–300 h of operation. Stainless steel materials used for impellers are taken to the required dimension and are given Alumina-Titania coating using detonation spray process. The thickness of the coating is 250 µm. The coated specimen is mounted in the work piece holder and subjected to erosion test using water Jet erosion tester. The parameters that are varied are exposure time, velocity of the jet and angle of impingement. Through this study it was found out that the most influencing factors of Liquid impact erosion are impact Angle and exposure time. It is observed that maximum erosion takes place when the impact angle is 90 degrees The SEM images reveal that the material removal takes place due to chipping and micro cutting. This occurs when the angle of impingement is 90° and the velocity of impingement is reasonably higher.